Total Phenolic and Antioxidant Capacity of Acetone Extract of Tristaniopsis merguensis Leaves - Occa Roanisca; Robby Gus Mahardika; Fajar Indah Puspita Sari (Stannum : Jurnal Sains dan Terapan Kimia, 2019)
The purpose of this study was to determine the total phenolic and antioxidant capacity of Tristaniopsis merguensis leaf acetone extract. In this study extraction using the maceration method for 3 days with a ratio of dry leaves and solvents of 1: 10 (w / v). Analysis of total polyphenols in this study was carried out using the Follin-Ciocalteu method. Total polyphenols were measured based on gallic acid standards. The antioxidant capacity is calculated based on the DPPH method. The results of this study, obtained extract yield of 9.34%. The total phenolic content of the Tristaniopsis merguensis leaf acetone extract was 215.22 mg GAE / g DW. While the antioxidant capacity of the acetone extract has an IC50 value of 22,1454 µg / mL.